Assessment of different plume-tracing algorithms for indoor plumes. (15th April 2020) - Li, Zeqi; Tian, Zhao Feng; Lu, Tien-fu; Wang, Houzhi
Abstract: Bio-inspired chemical plume-tracing methods have been applied in robots to detect chemical emissions and to localise the plume sources in both indoor and outdoor environments. In the first part of this study, a comparison of performance of several widely used plume-tracing algorithms was conducted. A plume-tracing algorithm can be divided into three stages for analysis: plume sensing, plume tracking and source localisation. These algorithms, which had been previously presented and tested in either simulation framework in 2D scenarios or experiments, were tested and compared in two different 3D scenarios in this study. In one scenario, a chemical source is located away from walls in a channel and in the other scenario, the chemical source is located near a wall. This is the first time that the performance of different plume-tracing algorithms in wall plumes has been tested and assessed and included in the literature. Sixteen different algorithms were tested and compared and the algorithm constituted by normal casting, surge anemotaxis and normal stepsize performed the best among all. In the second part of the study, this algorithm was further optimised by an 'along-wall' obstacle avoidance method and finally a novel algorithm, named vallumtaxis, was proposed and shown to achieve higher efficiency. Highlights: Various plume-tracing algorithms tested and assessed in wall plumes and free plumes. Normal casting, surge anemotaxis and constant stepsize together performing the best. Vallumtaxis with 'along-wall' obstacle avoidance method proposed. The robot with vallumtaxis proved to perform well in wall plumes.